Pengaruh Tingkat Imitasi Dan Kosmopolitan Wanita Tani Terhadap Keputusan Pengelolaan Usahatani - Suharyani, Anita; Oktoriana, Shenny (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2018)
The aims of this study are to analyze cosmopolitan and imitation levels of women farmers, and the influence of cosmopolitan and imitation levels of women farmers towards decision of farming management. This study was conducted in Limbung Village, Kubu Raya District, West Kalimantan. Respondent in this study consist of 26 womens who joint in women farmers group and 38 womens who do not joint in women farmers group. The method that used in this study are descriptive analyze and corelation analyze. The results showed that imitation level of women farmers group women farmers group is in average level. Beside that, the cosmopolitan level of women farmers group women farmers group is in high level. The result also showed that there is corelation between imitation and cosmopolitan levels has significant influence in decision of management farming